ULTRAVIOLET– B LIGHT INDUCED CHANGES IN ENERGY TRANSFER OF PHOTOSYSTEM II IN THE INTACT CELLS OF SPIRULINA PLATENSIS - B. PRAVEEN KUMAR,; S. ARIF MOHAMMAD,; D. GUNA SEKHAR,; S. D. S. MURTHY, (The Bioscan, 2010)
In this investigation an attempt has been made to study the effect of Ultraviolet-B (UV-B) radiation (2 Wm-2) on spectral properties of light harvesting complex (LHC) and energy transfer in the cyanobactrium, Spirulina platensis. Our results clearly indicated that there are alterations in the spectral properties as evidenced from the shift in both absorption and fluorescence emission peaks of phycocyanin (PC). PAM fluorescence studies clearly indicated that there is a rise in the F0 value which reflects the alterations of LHC in the above cyanobacterium.